2022
DOI: 10.3390/antiox11071343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gold Nanoparticles Functionalized with Bioactive Compounds from Cornus mas Fruit on Aorta Ultrastructural and Biochemical Changes in Rats on a Hyperlipid Diet—A Preliminary Study

Abstract: Cornus mas L. extract (CM) presents hypolipidemic, antioxidant and anti-inflammatory activity. Gold nanoparticles (AuNPs) are considered potent delivery systems and may be used to release pharmaceutical compounds at the level of injury. In our study, we used gold nanoparticles functionalized with bioactive compounds from Cornus mas L. (AuNPsCM) in an experimental model of a high-fat diet (HFD), and we assessed their effects on aorta wall but also in the serum, as compared to Cornus mas (CM) administration. Spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 70 publications
4
11
0
Order By: Relevance
“…SOD is in charge of limiting oxidative damage [38] and according to our results, SOD enzyme activity decreased in the HFD compared to the control and increased in the HFD + C. mas and HFD post-treated C. mas compared to the HFD. The protective effect of C. mas extract as an antioxidant was more favorable compared to atorvastatin treatment.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…SOD is in charge of limiting oxidative damage [38] and according to our results, SOD enzyme activity decreased in the HFD compared to the control and increased in the HFD + C. mas and HFD post-treated C. mas compared to the HFD. The protective effect of C. mas extract as an antioxidant was more favorable compared to atorvastatin treatment.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, GSH levels increased in the groups fed with iridoid loganic acid (CH+LA; 20 mg/kg body weight + 1% cholesterol) and anthocyanins (CH+ANT; 10 mg/kg body weight+1% cholesterol) obtained from C. mas for 60 days compared to the CH group [37]. A recent study reported that the concentration of GSH in rat serum was decreased in a high-fat diet compared to the control but increased significantly in the serum of rats treated with simple C. mas extract compared to the HFD group (p < 0.05) [38]. Overall, these studies substantiated our results and highlighted the beneficial effects of C. mas on the GSH level.…”
Section: Discussionmentioning
confidence: 99%
“…The level of the gold nanoparticles in the aorta wall was determined with ICP–OES (inductively coupled plasma–optical emission spectrometry) using a Perkin Elmer OPTIMA 2100 DV spectrometer, following the method that was described in our previous article [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The high-fat food was administered by gavage, bringing an additional 45% level of energy. The composition of the diet was described in our preliminary study [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation